The growth test of tea clones (Camellia sinensis) from cross pollination first generation clones - Vitria Puspitasari Rahadi; Heri Syahrian; Bambang Sriyadi (Jurnal Penelitian Teh dan Kina, 2016)
Efforts to improve the productivity of tea needed new high yielding clones were obtained from the cross and easily propagated vegetatively. Preliminary testing of the clonesÂ  needs to be done to determine the growth of cuttings and rooting properties of tea clones from hybridization which are selected by potential production. This study used a Randomized Complate Block Design with three replications. The treatments consist of 14 clones from crosses and GMB 7 as clone comparison. The data is analyzed by using ANOVA and Scott Knott test with the level of 5%. The observations are intended to look at the growth of roots and shoots by dismantling seedling in polybag predetermined randomly at each observation. The results showed that the clones tested had good growth with a low mortality rate, and easily propagated vegetatively. The S / R ratio also showed shoot growth more faster than the growth of root. This character is advantageous because the most appropriate selection criteria for planting in the field.